(untitled) (Jurnal Manajemen Pembangunan Daerah, 2019)
Bekasi City is a region which its growth rate of economic and population increase quite rapidly. Thus, supporting facilities and infrastructure development is necessary as it was in one of RPJMD mission 2008-2013. Methods were applied in this research are: 1) Analysis of quality targets of RPJMD program; 2) Analysis of the relevance, efficiency and effectiveness of programs and activities in APBD; 3) Identifing factors influencing the unconformity; 4) Formulating criteria and strategy alternatives through AHP; and 5) Final formulation of the alignment strategy. Result of this research showed some disharmonies both in program and activities planning of APBD and RPJMD caused by factors including: 1) Technology and system in the implementation of planning projects; 2) Endorsement for regional planning officers; 3) Leadership in accelerating the target achievement; 4) Human resources in SKPD; 5) Organization structure and SKPD planning team; also 6) Budget planning and preparation. Above all, strategy of alignment APBD planning with RPJMD has been formulated as follows: 1) Performance improvement of TAPD; 2) Performance improvement through ISO planning; 3) Participation increase in Musrenbang; 4) Communication and commitment of target achievement; 5) Apparatus training and application of functional planner position; 6) Incentive regulation and disincentives implementation; and 7) Draft program completion. Keywords: APBD, Bekasi City, RPJMD, Facilities and Infrastructure Development Strategy ABSTRAK Kota Bekasi merupakan kawasan dengan peningkatan laju pertumbuhan ekonomi dan populasi yang cukup tinggi. Oleh karena itu dukungan terkait pengembangan sarana dan prasarana di dalam kota menjadi penting seperti tertuang dalam salah satu misi RPJMD 2008-2013. Metode yang digunakan dalam penelitian ini antara lain: 1) Analisis kualitas sasaran program RPJMD; 2) Analisis relevansi, efesiensi dan perkiraan efektifitas program dan kegiatan dalam APBD; 3) Identifikasi faktor yang mempengaruhi ketidakselarasan; 4) Perumusan kriteria dan alternatif strategi serta penilaian bobot strategi melalui metode AHP serta 5) Perumusan akhir strategi penyelarasan. Berdasarkan hasil penelitian diperoleh gambaran bahwa terdapat beberapa ketidakselarasan dalam perencanaan kegiatan dan program APBD dengan RPJMD yang disebabkan oleh beberapa faktor, meliputi: 1) Teknologi dan sistem dalam pelaksanaan pekerjaan perencanaan; 2) Dukungan kepada aparatur perencana daerah; 3) Pimpinan dalam mendorong percepatan pencapaian sasaran; 4) Sumberdaya manusia di SKPD; 5) Struktur organisasi dan tim perencanaan SKPD serta 6) Perencanaan dan penyusunan anggaran. Dari hasil tersebut diperoleh rumusan strategi sebagai berikut: 1) Peningkatan kinerja TAPD; 2) Peningkatan kinerja dengan ISO perencanaan; 3) Peningkatan partisipasi dalam Musrenbang; 4) Komunikasi dan komitmen pencapaian sasaran; 5) Diklat aparatur dan penerapan jabatan fungsional perencana; 6) Penerapan regulasi insentif dan disinsentif; dan 7) Penyempurnaan rancangan program. Kata kunci: APBD, Kota Bekasi, RPJMD, Strategi Pengembangan Sarana dan Prasarana